PENGARUH PENGELOLAAN KELAS TERHADAP KONSENTRASI BELAJAR SISWA DALAM PEMBELAJARAN IPS DI SMPN 35 PEKANBARU - Yunanda, Fresti Vera; Indrawati, Henny; Haryana, Gani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to determine how much influence classroom management has on the concentrtion of student learning in IPS learning at SMP 35 Pekanbaru. This research is a quantitative descriptive study using simpel linear regression with the help of the SPSS program. Sampling techniques proportionate random sampling with a total sample of 143 students. The results of this study indicate that class management is in the good categor, while the learning concentration of students includes a fairly good category. From the test results it can be seen that calssroom management has a positive and significant effect on student learning concentration. Meaning if the management of the class is good then the concentration of student learning will be good too.Key Words: Class Management, Concentration Of Learning.